2012
DOI: 10.1111/j.1939-1676.2012.00894.x
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Prognostic Potential of Serum High‐Sensitivity Cardiac Troponin I and N‐Terminal pro‐B‐Type Natriuretic Peptide Concentrations in Dogs with Degenerative Mitral Valve Disease

Abstract: Background: Identification of factors associated with decreased survival in dogs with degenerative mitral valve disease (DMVD) will allow more accurate prognosis. N-terminal pro-B-type natriuretic peptide (NT-proBNP) is negatively associated with survival in dogs with DMVD. In human patients, multimarker strategies provide superior risk stratification compared with single markers.Hypothesis: High-sensitivity cardiac troponin I (hscTnI) and other clinical variables will be associated with survival time in dogs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
97
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(117 citation statements)
references
References 22 publications
15
97
1
3
Order By: Relevance
“…In agreement with a previous study (Hezzell et al, 2012), there was strong evidence for an 312 association between age and all-cause mortality in dogs with DMVD, with hazard of death 313 increasing 3.85 fold (95% CI: 2.61 -5.69) for each 5 year increase in age at diagnosis. In 314 addition to being an independent predictor of outcome, age at diagnosis confounded the 315 associations between breed and hazard of death, highlighting the importance of multivariable 316 analyses when interpreting the effect of explanatory variables in epidemiological studies.…”
Section: Cases 115supporting
confidence: 89%
“…In agreement with a previous study (Hezzell et al, 2012), there was strong evidence for an 312 association between age and all-cause mortality in dogs with DMVD, with hazard of death 313 increasing 3.85 fold (95% CI: 2.61 -5.69) for each 5 year increase in age at diagnosis. In 314 addition to being an independent predictor of outcome, age at diagnosis confounded the 315 associations between breed and hazard of death, highlighting the importance of multivariable 316 analyses when interpreting the effect of explanatory variables in epidemiological studies.…”
Section: Cases 115supporting
confidence: 89%
“…1,10 In addition, studies have shown that the presence of elevated levels of NT-proBNP may be an indicator to assist in predicting the first onset of congestive heart failure in dogs with mitral valve disease as well as prognostic information on survival. 8,9,11,12,17 A first-generation immunoassay for the quantitative measurement of NT-proBNP in canine plasma a provided reproducible results from ethylenediamine tetra-acetic acid (EDTA) plasma samples in a range of 50-3000 pmol/l with coefficients of variation (CVs) for intra-and interassay precision of <15% across the full range of the assay. 1,14 The enzyme-linked immunosorbent assay (ELISA) utilized 2 affinity-purified sheep anti-canine NT-proBNP polyclonal antibodies, one on the solid phase capture and another in the liquid detection reagent.…”
Section: Introductionmentioning
confidence: 99%
“…Increased plasma NP concentrations have been identified in dogs with dilated cardiomyopathy (DCM) 2, 3, 4, 5, 6, 7. Furthermore, NP concentrations have been shown to increase with increasing disease severity in dogs with myxomatous mitral valve disease (MMVD),3, 8, 9, 10, 11 and NT‐proBNP has been suggested to be predictive of outcome in dogs with MMVD 9, 12, 13, 14, 15, 16. Natriuretic peptides also have been found useful to distinguish CHF from respiratory disease 12, 17, 18, 19, 20.…”
mentioning
confidence: 99%